The house of the mosque - Abdolah, Kader 1954- (Canongate, 2011)
Iran, 1950. Spring has arrived, and as the women prepare the festivities, Sadiq waits for a suitor to knock on the door. Her uncle Nosrat returns from Tehran with a glamorous woman, while on the rooftop, Shahbal longs only for a television to watch the first moon landing. But not even the beloved grandmothers can foresee what will happen in the days and months to come.